Financování projektu z fondů EU - Mordová, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Bakalářská práce je zaměřena na čerpání finančních prostředků ze strukturálních fondů EU. Teoretická část představuje hlavní principy, jak Evropská Unie tyto prostředky poskytuje. Zabývá se pojetím regionální politiky a fondů EU. Najdeme v ní přehled jednotlivých programů, z kterých lze čerpat. Praktická část je vytvořena s cílem využít daných poznatků z teoretické části k vytvoření návrhu projektu na rekonstrukci penzionu pro účely konkrétní společnosti.

The bachelor thesis is focused on financial resources from Structural Funds European Union. Theoretical part is concentrated on the main knowledge, how the European Union distributes these resources. This part deal with conception of regional politics and funds, include summary of individual programs, from which can be drawn. Practical part is created with the objective to demonstrate how the formal facts and processional methods from theoretical part can be used for submission of an proposal of projekt which can be used for purposes company.
Financing of Project from European Union Funds
Keywords: Regionální politika EU; strukturální fondy; operační programy; projekt; analýza; Regional politics EU; sturctural funds; operational programs; project; analysis